The Effect Of Collaborative Writing Technique Through Students’ Writing Announcement Text At Second Grade In Smp N 3 Bonjol - Syafitry, Nova; Kardena, Absharini (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2021)
This research was due to discover the effect of collaborative writing technique through students’ writing announcement at second grade in SMP N 3 BONJOL because some of students in SMP N 3 BONJOL still had problems in master english especially in writing text. Some of the students had a problems in making paragraph clearly, in organizing their ideas, to found their grammatical or vocabulary error and etc. The research used experimental research, the researcher used quasi experimental design by using pretest-posttest design. The data was through pre-test and post-test to experimental and control class. To analyze the data, the researcher used the normality by using lilifors test and the homogenity test by using F test and to test the hypothesis the researcher used t-test formula and consulted the result into t-table with level of significant Î±=0.05. From the result and accounting the pretest and posttest scores of experimental class, it was found using collaborative writing technique in writing had better result than using conventional technique.